Library Management and Human Development in John Harris Library, University Of Benin - Eneh , Anthonia C.; Opara , Vincent C. (Communicate: Journal of Library and Information Science, 2024)
The study investigated library management and human resource development in John Harris Library, University of Benin, Benin City. The study adopted a correlational research survey design. The population of the study was 63 comprising the entire library staff of John Harris Library. The total enumeration technique was adopted to cover all sixty three (63) library staff in John Harris Library. The instrument used was questionnaire titled “Library management and Human Resource Development Questionnaire in John Harris University library (LMHRDQJHUL)”. Out of 63 copies of the questionnaire distributed, 55 were found valid for analysis. Mean score and standard deviation was used to answer the research questions. The result shows that there is a significant relationship between staff appraisal and human resource development (correlation coefficient of r=811), training and human resource development (correlation coefficient of r=722) and innovative culture and human resource development (correlation coefficient of r=545), in John Harris library, University of Benin. The study recommended among other things that library staff appraisal should be strengthened, training should be organized and innovative culture should be strengthened to enhance staff development.